Substantiation of organizational and technological solutions for construction within the “car-free city” concept - Beliakov Sergei (MATEC Web of Conferences, 2018)
In the article, the author developed the classification of the main models of implementation of the “car-free city” concept depending on organizational and technological solutions in the construction and reconstruction of the urban environment. The author determined that the problem of selecting the optimal model should be decided on the basis of a comprehensive analysis of various factors that determine the specific features and problems of a specific urban situation (social, technical, organizational, environmental, cultural, economic, climatic, etc). The developed solution should meet the criteria of ensuring the comfort of the urban environment and investment attractiveness. The author developed the basic algorithm of choosing the optimal organizational and technological solutions for the development of urban development within the “car-free city” concept, the use of which will contribute to maximizing socio-economic, environmental and other effects while ensuring the investment attractiveness and competitiveness of construction project decisions.